Extrusion-molded magnesium oxide tube and processing technology thereof
By using a combination of magnesium oxide, inorganic auxiliary materials and specific binders, and using ball milling and hot pressing curing processes, the quality problems caused by hydration reaction of magnesium oxide products during sintering are solved, and the preparation of high-quality magnesium oxide tubes is achieved, with excellent thermal shock resistance, erosion resistance and thermal conductivity.
Patent Information
- Application Number
- CN202510068604.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The hydration reaction caused by the aqueous binder during the sintering process of existing magnesium oxide products affects the extrusion performance and sintering quality.
A combination of 92 to 96 parts of magnesium oxide, 4 to 8 parts of inorganic auxiliary materials, and 1 to 16 parts of cellulose binder or silicone binder is used to form a high-quality magnesium oxide tube through ball milling and hot pressing curing processes.
The thermal shock resistance, corrosion resistance and thermal conductivity of magnesium oxide tubes are improved, and the density and comprehensive thermal performance of sintered products are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional ceramics, in particular to an extruded magnesium oxide tube and a processing technology thereof. Background Art
[0002] Due to its good high-temperature insulation and thermal conductivity, magnesium oxide products are widely used in high-temperature insulation fields such as electric heating tubes, armored heating cables, and temperature measuring wires. As a functional ceramic, its products are often in the form of magnesium oxide tubes, which are obtained by mixing magnesium oxide with a binder, extruding, and then sintering. If the binder uses an aqueous reagent, it will cause the hydration of magnesium oxide to form magnesium hydroxide, which will seriously affect the extrusion performance of magnesium oxide, and the quality of the magnesium oxide tube formed after sintering is poor. Therefore, we propose an extruded magnesium oxide tube and its processing technology. Summary of the invention
[0003] The object of the present invention is to provide an extruded magnesium oxide tube and a processing technology thereof to solve the problems raised in the above background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solution: an extruded magnesium oxide tube, comprising the following components by mass: 92 to 96 parts of magnesium oxide, 4 to 8 parts of inorganic auxiliary materials, and 1 to 16 parts of a binder.
[0005] Furthermore, the inorganic auxiliary material is a mixture of one or more of silicon dioxide, aluminum oxide, titanium dioxide, magnesium fluoride, and titanium boride.
[0006] Furthermore, the binder is one of a cellulose binder and an organosilicon binder, or a mixture of the two.
[0007] A processing technology for extruded magnesium oxide tubes, comprising the following processes: The magnesium oxide and inorganic auxiliary materials are mixed and ball-milled; a binder is added, extruded and sintered to obtain a magnesium oxide tube.
[0008] Furthermore, the process conditions of ball milling are: a rotation speed of 300-500 r / min, a duration of 3-6 hours, and then sieved through a 300-600 mesh sieve. 2-4wt% oleic acid is added during ball milling to assist the ball milling. After ball milling and sieving, magnetic conveying is performed to remove iron from the powder.
[0009] After extrusion molding, the products are dried, cut and laid flat, air-dried, bundled, cut, blown into powder, and packed in saggers. They are then sintered at high temperature (the above sintering), and inspected and packaged after sintering.
[0010] Furthermore, the sintering process conditions are as follows: heating from room temperature to 1000°C at a rate of 10°C / min; heating to 1520-1600°C at a rate of 5°C / min, keeping warm for 2-3h; then cooling to 500°C at a rate of 5°C / min, and cooling to room temperature in the furnace.
[0011] Furthermore, after ball milling, a boric acid compound is added to magnesium oxide and inorganic auxiliary materials, mixed, and stirred at a rotation speed of 300 to 500 rpm for 10 to 30 minutes.
[0012] Furthermore, the inorganic auxiliary material is a mixture of aluminum oxide and titanium boride in a mass ratio of (0.5-3.0):1.
[0013] In the above technical scheme, nano-alumina is selected as an inorganic auxiliary material to participate in the solid phase sintering of magnesium oxide. The tiny particles of nano-alumina are dispersed around the magnesium oxide grains through diffusion, and gradually diffuse to the magnesium oxide grain boundaries and grain boundary pores as the sintering reaction proceeds, and react with magnesium oxide in a solid phase to generate magnesium aluminum spinel phase, and as the amount of alumina increases, the magnesium aluminum spinel phase grains gradually grow, pinned at the grain boundaries, fill the pore positions, inhibit the grain boundary movement of magnesium oxide grains, and hinder their growth, thereby promoting the densification of the sintered product system structure, and its densification degree deepens with the increase of sintering temperature. The doping of the magnesium aluminum spinel phase formed in the sintered product in the magnesium oxide sintered product can effectively improve the thermal shock stability and corrosion resistance of the sintered product, and at the same time, its thermal conductivity is high, which can assist in improving the high temperature resistance and thermal conductivity of the sintered product, and is more suitable for the use environment of the magnesium oxide tube.
[0014] Titanium boride has high hardness, thermal conductivity and high temperature resistance, and can effectively improve the strength, hardness, high temperature resistance and thermal conductivity of magnesium oxide sintered products. When it is used as an inorganic auxiliary material and mixed with magnesium oxide and aluminum oxide for sintering, it is partially oxidized to form an oxidation product, titanium dioxide, which can replace aluminum oxide and synthesize magnesium titanate with magnesium oxide, further improving the thermal stability, high temperature resistance and insulation properties of the sintered products.
[0015] Further, the amount of the boric acid compound is 3.9 to 10% of the mass of the binder; The boronic acid compound is one of aminophenylboronic acid, pyridine-4-boric acid, 4-pyrazoleboric acid, 5-pyrimidineboric acid, (2-methylpyrimidin-5-yl)boric acid, 2-aminopyrimidine-5-boric acid and 6-aminopyridineboric acid.
[0016] Furthermore, the binder is one of hydroxy silicone resin and polycarbosilane or a mixture of the two. The polycarbosilane is prepared by the following process: Under the protection of nitrogen atmosphere, chloromethyltrichlorosilane and magnesium are mixed in tetrahydrofuran, polychlorosilane is slowly added, and the mixture is reacted at 55-65°C for 15-20 hours; the mixture is cooled to 45-52°C, an alcohol compound is added, and the mixture is refluxed for 3-5 hours; the pH value of the mixture is adjusted to neutral by rotary evaporation, the mixture is filtered, the precipitate is washed, and the mixture is dried to obtain polycarbosilane.
[0017] Furthermore, the polychlorosilane is a mixture of one or more of 1,1,3,3-tetrachloro-1,3-disiloxane, bis(trichlorosilyl)methane, and 1,2-dimethyl-1,1,2,2-tetrachlorodisilane.
[0018] Further, the molar ratio of chloromethyltrichlorosilane to polychlorosilane is 10:(0.5-2.0); The ratio of chloromethyltrichlorosilane, magnesium (chips), and tetrahydrofuran is 10g: (1.5-2.7)g: (50-200)mL.
[0019] Further, the alcohol compound is ethanol or methanol; The molar ratio of polychlorosilane to alcohol compound is 1:(1.5-2.2).
[0020] Furthermore, when the above-mentioned adhesive is used, hot pressing curing is performed after extrusion molding, and the process is as follows: heat to 100°C, increase the temperature to 120-150°C at a rate of 5°C / min under a pressure of 6-12MPa, and keep the temperature and pressure for 30-60min; then cool to room temperature.
[0021] In the above technical scheme, powder is mixed with boric acid compound, boric acid compound is loaded on the surface of powder, and an organic coating layer is formed, which can effectively suppress the agglomeration and sedimentation of powder, improve the compatibility and dispersibility between powder and binder, obtain better processing fluidity, and improve the extrusion processing ability of mixing. Under hot pressing curing conditions, boric acid compound and binder undergo cross-linking curing reaction, form a network structure coated on the surface of powder, form an organic coating layer, construct the interface structure of powder and binder, improve the extrusion ability of mixture, and preliminarily fix the product to be sintered, which can effectively resist the shrinkage and deformation during sintering, prevent the deformation caused by thermal stress deformation caused by temperature gradient, the residual stress generated by pressing is released at high temperature, the pores in the product to be sintered, crack expansion, etc., prevent sintering collapse and particle shedding to a certain extent, and improve sintering quality. Boric acid compound selects nitrogen-containing boric acid compound, which has stronger adsorption with powder, and has better compatibility with binder, participates in condensation reaction, and promotes system curing.
[0022] In the above technical scheme, during the sintering process, the organic groups such as methyl, hydroxyl, phenyl on the side chain of the binder component undergo chemical reactions such as oxidation, dehydrogenation, and decomposition, resulting in thermal cracking behavior and overflowing gaseous volatiles. Its components, carbon monoxide, water, and oxygen in the sintering atmosphere can react with boron carbide to produce a ceramic reaction, which reduces the influence of gas on the quality of the sintered product to a certain extent, forms a refractory ceramic phase (boron oxide, titanium oxide), and improves the strength of the sintered product; the degree of doping with aluminum oxide, magnesium oxide, etc. increases, thereby improving the thermal stability, high temperature resistance and electrical insulation properties of the sintered product; as the temperature rises, the silicon-oxygen bonds of the main chain of the binder break and rearrange, and the silicon methyl is thermally oxidized. The rigid groups and high bond energy BO bonds in the boric acid compound can delay the degradation of the binder at high temperature, thereby promoting the ceramic reaction and realizing the organic-inorganic ceramic transformation; the hydroxy silicone resin contained in the binder forms silicon dioxide after sintering, diffuses and reacts with MgO The solid phase reaction can cooperate with the above ceramic phase as a reinforcing phase to fill the pores between the magnesium oxide particles, making the magnesium oxide particles more densely bonded, promoting the formation of sintering necks between the particles, alleviating the thermal resistance caused by the pores, and improving the heat transfer efficiency between the magnesium oxide particles, thereby improving the strength and comprehensive thermal properties of the sintered products, such as thermal conductivity and thermal shock resistance.
[0023] The binder also contains polycarbosilane, which is obtained by coupling a Grignard reagent prepared from chloromethyltrichlorosilane and magnesium with polychlorosilane and then hydrolyzing it. The product has a branched structure and multiple hydroxyl groups, which can effectively reduce the viscosity of the binder, reduce the use of water in the binder, and prevent the hydration of magnesium oxide. The cross-linking of polycarbosilane and boric acid compounds enables the product formed after hot pressing and curing to resist thermal stress deformation during the sintering process, alleviate the negative impact of residual stress, vibration, and impact on the sintered product, and improve the degree of cross-linking between the binder and the boric acid compound, which effectively promotes the close bonding between the powders.
[0024] After sintering, polycarbosilane produces amorphous silicon carbide, silicon dioxide and carbon. The mixing and cross-linking of polycarbosilane with hydroxy silicone resin can help reduce the free carbon after sintering of polycarbosilane, alleviate its negative impact on the strength and insulation properties of the sintered products, and form three-dimensional silicon carbide ceramics between magnesium oxide particles, which can further improve the hardness, high temperature resistance and stability of the sintered products and improve their heat transfer efficiency. In addition, carbon can improve the thermal shock resistance of the sintered products, reduce the thermal expansion mismatch between magnesium oxide particles, enhance the material's ability to withstand rapid temperature changes, enhance the bonding between magnesium oxide particles, improve the material's mechanical strength and toughness, prevent particles from falling off and material collapse during sintering; it can also play a shielding role, prevent or reduce the reaction of oxygen in the sintered products at high temperatures, and improve the material's antioxidant capacity, so that the material has good comprehensive performance. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In the following specific implementations, Magnesium oxide (MgO): AR, average particle size 3.31 μm, from Sinopharm Chemical Reagent Co., Ltd.; Alumina (Al2O3): D50 = 1-1.8 μm, from Zhengzhou Xinli Wear-Resistant Materials Co., Ltd. Titanium boride (TiB2): RDB-NM-049, average particle size 1-3μm, from Shanghai Yanbei New Materials Technology Co., Ltd.; Silicon dioxide (SiO2): AR, average particle size 50 nm, from Shanghai Aladdin Biochemical Technology Co., Ltd.; Magnesium chips: purity> 99%, from Tianjin Hainachuan Technology Co., Ltd.; Hydroxy silicone resin: IOTA-8865H, from Anhui IOTA Silicone Oil Co., Ltd.; The extrusion molding is carried out in a vacuum extruder, and the process is: vacuum degree -0.090MPa, extrusion pressure 10MPa; When using the binder in Examples 1-3 and Comparative Examples 1-3, it was added in the form of an emulsion, and the "parts" referred to were the mass of the binder; the emulsion was formed by mixing the binder and water and stirring at a speed of 3000 rpm for 30 minutes, and the solid content of the emulsion was 54%.
[0027] Embodiment 1: A processing technology for extruded magnesium oxide tube, comprising the following processes: Step 1: Under the protection of nitrogen atmosphere, chloromethyltrichlorosilane and magnesium chips are mixed in tetrahydrofuran, polychlorosilane is slowly added, and the mixture is reacted at 55°C for 20 hours; cooled to 45°C, ethanol is added, and the mixture is refluxed for 5 hours; rotary evaporation is performed to adjust the pH of the system to neutral, the mixture is filtered, the precipitate is washed, and dried to obtain polycarbosilane; the polychlorosilane is 1,1,3,3-tetrachloro-1,3-disiloxane; the molar ratio of chloromethyltrichlorosilane to polychlorosilane is 10:0.5; the ratio of chloromethyltrichlorosilane, magnesium chips, and tetrahydrofuran is 10g:1.5g:50mL; the molar ratio of polychlorosilane to ethanol or methanol is 1:1.5; Step 2: Mix magnesium oxide and inorganic auxiliary materials, and ball mill. The process conditions of ball milling are: rotation speed 300r / min, duration 6h; then pass through a 600-mesh sieve, and add 2wt% oleic acid to assist ball milling; the inorganic auxiliary materials are a mixture of aluminum oxide and titanium boride, with a mass ratio of 3.0:1; Then, a boric acid compound is added and mixed, and stirred at a speed of 300 rpm for 10 minutes; the amount of the boric acid compound is 3.9% of the mass of the binder; the boric acid compound is aminophenylboric acid; Add a binder, extrude, hot press and cure, and sinter to obtain a magnesium oxide tube, which includes the following mass components: 96 parts of magnesium oxide, 4 parts of inorganic auxiliary materials, and 3 parts of a binder; the binder is a mixture of hydroxy silicone resin and polycarbosilane with a mass ratio of 4:1; the hot pressing and curing process is: heating to 100°C, heating to 120°C at a rate of 5°C / min under a pressure of 10MPa, keeping the temperature for 30 minutes, and cooling to room temperature; the sintering process conditions are: heating from room temperature to 1000°C at a rate of 10°C / min; heating to 1520°C at a rate of 5°C / min, keeping the temperature for 3 hours; then cooling to 500°C at a rate of 5°C / min, and cooling to room temperature with the furnace.
[0028] Embodiment 2: A processing technology for extruded magnesium oxide tube, comprising the following processes: Step 1: Under the protection of nitrogen atmosphere, chloromethyltrichlorosilane and magnesium chips are mixed in tetrahydrofuran, polychlorosilane is slowly added, and the mixture is reacted at 60°C for 18 hours; cooled to 48°C, ethanol is added, and the mixture is refluxed for 4 hours; rotary evaporation is performed to adjust the pH of the system to neutral, the mixture is filtered, the precipitate is washed, and dried to obtain polycarbosilane; the polychlorosilane is di(trichlorosilyl)methane; the molar ratio of chloromethyltrichlorosilane to polychlorosilane is 10:1.2; the ratio of chloromethyltrichlorosilane, magnesium chips, and tetrahydrofuran is 10 g:2.1 g:100 mL; the molar ratio of polychlorosilane to ethanol or methanol is 1:1.8; Step 2: Mix magnesium oxide and inorganic auxiliary materials, and ball mill. The process conditions of ball milling are: speed 400r / min, time 4.5h; then pass through a 600-mesh sieve, and add 3wt% oleic acid to assist ball milling; the inorganic auxiliary materials are a mixture of aluminum oxide and titanium boride, with a mass ratio of 1.8:1; Then, a boric acid compound is added and mixed, and stirred at a speed of 400 rpm for 20 minutes; the amount of the boric acid compound is 7.0% of the mass of the binder; the boric acid compound is 4-pyrazole boric acid; Add a binder, extrude, hot press and cure, and sinter to obtain a magnesium oxide tube, which includes the following mass components: 94 parts of magnesium oxide, 6 parts of inorganic auxiliary materials, and 6 parts of a binder; the binder is a mixture of hydroxy silicone resin and polycarbosilane with a mass ratio of 2.5:1; the hot pressing and curing process is: heating to 100°C, heating to 135°C at a rate of 5°C / min under a pressure of 12MPa, keeping the temperature for 45min, and cooling to room temperature; the sintering process conditions are: heating from room temperature to 1000°C at a rate of 10°C / min; heating to 1560°C at a rate of 5°C / min, keeping the temperature for 2.5h; then cooling to 500°C at a rate of 5°C / min, and cooling to room temperature with the furnace.
[0029] Embodiment 3: A processing technology for extruded magnesium oxide tube, comprising the following processes: Step 1: Under the protection of nitrogen atmosphere, chloromethyltrichlorosilane and magnesium chips are mixed in tetrahydrofuran, polychlorosilane is slowly added, and the mixture is reacted at 65°C for 15 hours; cooled to 52°C, ethanol is added, and the mixture is refluxed for 4 hours; rotary evaporation is performed to adjust the pH of the system to neutral, the mixture is filtered, the precipitate is washed, and dried to obtain polycarbosilane; the polychlorosilane is 1,2-dimethyl-1,1,2,2-tetrachlorodisilane; the molar ratio of chloromethyltrichlorosilane to polychlorosilane is 10:2; the ratio of chloromethyltrichlorosilane, magnesium chips, and tetrahydrofuran is 10 g:2.7 g:200 mL; the molar ratio of polychlorosilane to ethanol or methanol is 1:2.2; Step 2: Mix magnesium oxide and inorganic auxiliary materials, and ball mill. The process conditions of ball milling are: speed 500r / min, time length 3h; then pass through a 600 mesh sieve, and add 4wt% oleic acid to assist ball milling during ball milling; the inorganic auxiliary materials are a mixture of aluminum oxide and titanium boride, with a mass ratio of 3:1; Then, a boric acid compound is added and mixed, and stirred at a speed of 500 rpm for 30 minutes; the amount of the boric acid compound is 10% of the mass of the binder; the boric acid compound is 2-aminopyrimidine-5-boric acid; Add a binder, extrude, hot press and cure, and sinter to obtain a magnesium oxide tube, which includes the following mass components: 92 parts of magnesium oxide, 8 parts of inorganic auxiliary materials, and 9 parts of a binder; the binder is a mixture of hydroxy silicone resin and polycarbosilane, and the mass ratio is 1:1; the hot pressing and curing process is: heating to 100°C, and heating to 150°C at a rate of 5°C / min under a pressure of 15MPa, keeping the temperature for 60min, and cooling to room temperature; the sintering process conditions are: heating from room temperature to 1000°C at a rate of 10°C / min; heating to 1600°C at a rate of 5°C / min, keeping the temperature for 2h; then cooling to 500°C at a rate of 5°C / min, and cooling to room temperature with the furnace.
[0030] Comparative Example 1: A processing technology for an extruded magnesium oxide tube, comprising the following processes: Step 1: Under the protection of nitrogen atmosphere, chloromethyltrichlorosilane and magnesium chips are mixed in tetrahydrofuran, polychlorosilane is slowly added, and the mixture is reacted at 55°C for 20 hours; cooled to 45°C, ethanol is added, and the mixture is refluxed for 5 hours; rotary evaporation is performed to adjust the pH of the system to neutral, the mixture is filtered, the precipitate is washed, and dried to obtain polycarbosilane; the polychlorosilane is 1,1,3,3-tetrachloro-1,3-disiloxane; the molar ratio of chloromethyltrichlorosilane to polychlorosilane is 10:0.5; the ratio of chloromethyltrichlorosilane, magnesium chips, and tetrahydrofuran is 10g:1.5g:50mL; the molar ratio of polychlorosilane to ethanol or methanol is 1:1.5; Step 2: Mix magnesium oxide and inorganic auxiliary materials, and ball mill. The process conditions of ball milling are: rotation speed 300r / min, duration 6h; then pass through a 600-mesh sieve, and add 2wt% oleic acid to assist ball milling; the inorganic auxiliary materials are a mixture of aluminum oxide and titanium boride, with a mass ratio of 3.0:1; Add a binder, extrude, hot press and cure, and sinter to obtain a magnesium oxide tube, which includes the following mass components: 96 parts of magnesium oxide, 4 parts of inorganic auxiliary materials, and 3 parts of a binder; the binder is a mixture of hydroxy silicone resin and polycarbosilane with a mass ratio of 4:1; the hot pressing and curing process is: heating to 100°C, heating to 120°C at a rate of 5°C / min under a pressure of 10MPa, keeping the temperature for 30 minutes, and cooling to room temperature; the sintering process conditions are: heating from room temperature to 1000°C at a rate of 10°C / min; heating to 1520°C at a rate of 5°C / min, keeping the temperature for 3 hours; then cooling to 500°C at a rate of 5°C / min, and cooling to room temperature with the furnace.
[0031] Comparative Example 2: A processing technology for an extruded magnesium oxide tube, comprising the following processes: Mix magnesium oxide and inorganic auxiliary materials, and ball mill the mixture. The process conditions of ball milling are: rotation speed 300r / min, duration 6h; then pass through a 600-mesh sieve, and add 2wt% oleic acid to assist the ball milling; the inorganic auxiliary materials are a mixture of aluminum oxide and titanium boride, with a mass ratio of 3.0:1; Add a binder, extrude, hot press cure, and sinter to obtain a magnesium oxide tube, which includes the following mass components: 96 parts of magnesium oxide, 4 parts of inorganic auxiliary materials, and 3 parts of a binder; the binder is a hydroxy silicone resin; the hot pressing curing process is: heating to 100°C, heating to 120°C at a rate of 5°C / min under a pressure of 10MPa, keeping the temperature for 30 minutes, and cooling to room temperature; the sintering process conditions are: heating from room temperature to 1000°C at a rate of 10°C / min; heating to 1520°C at a rate of 5°C / min, keeping the temperature for 3 hours; then cooling to 500°C at a rate of 5°C / min, and cooling to room temperature with the furnace.
[0032] Comparative Example 3: A processing technology for an extruded magnesium oxide tube, comprising the following processes: Mix magnesium oxide and inorganic auxiliary materials, and ball mill them. The process conditions of ball milling are: speed 300r / min, duration 6h; then pass through a 600-mesh sieve, and add 2wt% oleic acid to assist ball milling during ball milling; the inorganic auxiliary material is aluminum oxide; Add a binder, extrude, hot press cure, and sinter to obtain a magnesium oxide tube, which includes the following mass components: 96 parts of magnesium oxide, 4 parts of inorganic auxiliary materials, and 3 parts of a binder; the binder is a hydroxy silicone resin; the hot pressing curing process is: heating to 100°C, heating to 120°C at a rate of 5°C / min under a pressure of 10MPa, keeping the temperature for 30 minutes, and cooling to room temperature; the sintering process conditions are: heating from room temperature to 1000°C at a rate of 10°C / min; heating to 1520°C at a rate of 5°C / min, keeping the temperature for 3 hours; then cooling to 500°C at a rate of 5°C / min, and cooling to room temperature with the furnace.
[0033] Comparative Example 4: A processing technology for an extruded magnesium oxide tube, comprising the following processes: Mix magnesium oxide and inorganic auxiliary materials, and ball mill them. The process conditions of ball milling are: speed 300r / min, duration 6h; then pass through a 600-mesh sieve, and add 2wt% oleic acid to assist ball milling during ball milling; the inorganic auxiliary material is silicon dioxide; Add a binder, extrude, dry, and sinter to obtain a magnesium oxide tube, which includes the following mass components: 96 parts of magnesium oxide, 4 parts of inorganic auxiliary materials, and 4 parts of a binder; the binder is a cellulose binder, specifically a 25wt% hydroxypropyl methylcellulose aqueous solution; the drying process conditions are: temperature 100°C, time 10 hours, and then cooling to room temperature; the sintering process conditions are: heating from room temperature to 1000°C at a rate of 10°C / min; heating to 1520°C at a rate of 5°C / min, and keeping warm for 3 hours; then cooling to 500°C at a rate of 5°C / min, and cooling to room temperature with the furnace.
[0034] Experiment: Take the magnesium oxide tubes obtained in Examples 1-3 and Comparative Examples 1-4, prepare samples, test their properties respectively and record the test results: Mechanical properties test: A universal testing machine was used to test the three-point bending strength of the sample in a 25°C experimental environment, with a span of 30 mm and a loading speed of 0.5 mm / min. Thermal performance test: Use an electrochemical workstation to test the resistivity of the sample at 600°C; Use a thermal conductivity tester to test the thermal conductivity of the sample and take the average value of the 250-950℃ pieces; Thermal shock resistance test: place the sample at 110℃ for 30 minutes, take it out and place it at 960℃ for 30 minutes; take it out and place it in 14℃ running water for rapid cooling for 3 minutes, take it out and dry it at 110℃ for 30 minutes, which is recorded as one thermal shock. Calculate the strength loss rate of the sample after 5 thermal shocks.
[0035]
[0036] According to the data in the above table, we can clearly draw the following conclusions: The magnesium oxide tubes obtained in Examples 1-3 were compared with the magnesium oxide tubes obtained in Comparative Examples 1-4. The test results show that: Compared with the comparative example, the magnesium oxide tubes obtained in Examples 1-3 have higher resistivity, thermal conductivity, bending strength data and lower thermal shock strength loss, which fully demonstrates that the present invention achieves improvement in mechanical properties and thermal properties of the magnesium oxide tubes.
[0037] Compared with Example 1, in Comparative Example 1, no boric acid compound is added; in Comparative Example 2, no boric acid compound and polycarbosilane are added, and the magnesium oxide tube is made of magnesium oxide, aluminum oxide, titanium boride, and hydroxy silicone resin; in Comparative Example 3, no boric acid compound, polycarbosilane, and titanium boride are added, and the magnesium oxide tube is made of magnesium oxide, aluminum oxide, and hydroxy silicone resin; in Comparative Example 4, the magnesium oxide tube is prepared from magnesium oxide, silicon dioxide, and hydroxypropyl methylcellulose. The magnesium oxide tubes obtained in Comparative Examples 1-4 have decreased resistivity, thermal conductivity, and flexural strength data, and increased thermal shock strength loss. It can be seen that the arrangement of the magnesium oxide tube components and their processes in the present invention can promote the comprehensive improvement of its mechanical properties and thermal properties.
[0038] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A processing technology for extruded magnesium oxide tube, characterized in that: Including the following processes: The magnesium oxide and inorganic auxiliary materials are mixed and ball-milled; a binder is added, extruded and formed, and sintered to obtain a magnesium oxide tube; The inorganic auxiliary material is a mixture of aluminum oxide and titanium boride.
2. The processing technology of an extruded magnesium oxide tube according to claim 1, characterized in that: The magnesium oxide tube comprises the following components by weight: 92 to 96 parts of magnesium oxide, 4 to 8 parts of inorganic auxiliary materials, and 1 to 16 parts of a binder.
3. The processing technology of an extruded magnesium oxide tube according to claim 1, characterized in that: After ball milling, the boric acid compound is added to the magnesium oxide and the inorganic auxiliary material, and the mixture is stirred at a rotation speed of 300 to 500 rpm for 10 to 30 minutes.
4. The processing technology of the extruded magnesium oxide tube according to claim 3 is characterized in that: The boric acid compound is one of aminophenylboric acid, pyridine-4-boric acid, 4-pyrazoleboric acid, 5-pyrimidineboric acid, (2-methylpyrimidine-5-yl)boric acid, 2-aminopyrimidine-5-boric acid and 6-aminopyridineboric acid; the amount of the boric acid compound used is 3.9-10% of the mass of the binder.
5. The processing technology of the extruded magnesium oxide tube according to claim 1, characterized in that: The binder is one of hydroxy silicone resin and polycarbosilane or a mixture of the two. Polycarbosilane is prepared by the following process: Under the protection of nitrogen atmosphere, chloromethyltrichlorosilane and magnesium are mixed in tetrahydrofuran, polychlorosilane is slowly added, and the reaction is carried out at 55-65°C for 15-20h; Cool to 45-52° C., add an alcohol compound, and reflux for 3-5 hours; perform rotary evaporation to adjust the pH of the system to neutral, filter, wash and dry the precipitate to obtain polycarbosilane.
6. The processing technology of the extruded magnesium oxide tube according to claim 5, characterized in that: The polychlorosilane is a mixture of one or more of 1,1,3,3-tetrachloro-1,3-disiloxane, bis(trichlorosilyl)methane, and 1,2-dimethyl-1,1,2,2-tetrachlorodisilane.
7. The processing technology of the extruded magnesium oxide tube according to claim 5, characterized in that: The molar ratio of chloromethyltrichlorosilane to polychlorosilane is 10:(0.5-2.0)7.
8. The process for processing an extruded magnesium oxide tube according to claim 5, characterized in that: The alcohol compound is ethanol or methanol; the molar ratio of polychlorosilane to the alcohol compound is 1:(1.5-2.2).
9. The processing technology of the extruded magnesium oxide tube according to claim 5, characterized in that: When the above-mentioned adhesive is used, hot pressing curing is carried out after extrusion molding, and the process is as follows: heat to 100°C, and at a pressure of 10 to 15 MPa, heat to 120 to 150°C at a rate of 5°C / min, and keep the temperature and pressure for 30 to 60 minutes; then cool to room temperature.
10. An extruded magnesium oxide tube obtained according to the processing technology described in any one of claims 1 to 9.
Citation Information
Patent Citations
Flexible composite ceramic heat conduction material and preparation method thereof
CN106145903A
Preparation method of titanium diboride metal ceramic
CN107188566A
Preparation method of extruded magnesium oxide tube
CN108516804A
Method and device for preparing high-density magnesium oxide tube
CN118290124A
Production of formed magnesia
JP1995165460A
Cited By
High-activity and high-purity titanium boride powder for energy storage of lithium ion battery and preparation method of high-activity and high-purity titanium boride powder
CN122187063A